PESANTREN HID AYATULLAH GUNUNG TEMBAK DAN ISSU TERORISME - Abdul Kadir Ahmad (Al-Qalam, 2007)
This research was conducted in Balikpapan, East Kalimantan. This researchaims to describe relation between Pesantren Hidayatullah andterrorism issue. Data was collected using interview and observation.Data was analyzed by descriptive analysis..This research indicates that vision, mission and all education programof Pesantren Hidayatullah doesn't relate to terrorism issue. The programsof Pesantren Hidayatullah are education in all degrees, informaleducation such as course, cadre et al, and also social and economicprogram. So, the accusation that Pesantren Hidayatullah is part of globalterrorism was lied.